2008
DOI: 10.1017/s1460396908006316
|View full text |Cite
|
Sign up to set email alerts
|

Variations in inter-observer contouring and its impact on dosimetric and radiobiological parameters for intensity-modulated radiotherapy planning in treatment of localised prostate cancer

Abstract: Inter-observer variations in contouring and their impacts on dosimetric and radiobiological parameters in intensity-modulated radiotherapy (IMRT) treatment for localised prostate cancer patients were investigated. Four observers delineated the gross tumour volume (GTV) (prostate and seminal vesicles), bladder and rectum for nine patients. Contouring done by radiologist was considered as gold standard for comparison purposes and for IMRT plan optimisation. Maximum average variations in contoured prostate, bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Therefore, the model can be easily shared by creating pseudo-structures at each institute. It was also reported that inter-observer contouring variations have a signi cant impact on dosimetric and radiobiological outcomes in intensity modulated radiation therapy planning [36]. Reducing the number of structures is useful as a means of homogenizing treatment plan quality across institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the model can be easily shared by creating pseudo-structures at each institute. It was also reported that inter-observer contouring variations have a signi cant impact on dosimetric and radiobiological outcomes in intensity modulated radiation therapy planning [36]. Reducing the number of structures is useful as a means of homogenizing treatment plan quality across institutions.…”
Section: Discussionmentioning
confidence: 99%
“…DV can stem from multiple sources, including inter-observer variability (i.e. multiple delineators will not generate precisely the same structures) (Bhardwaj et al 2008, Caravatta et al 2014, Xu et al 2016, intra-observer variability (i.e. the same delineator will not generate precisely the same structures in two different sessions) (Fiorino et al 1998, Petric et al 2008, Xu et al 2016, and methodological variability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ROIs are mostly segmented manually by physicians or dosimetrists prior to their use in treatment planning. While manual contouring is the clinical standard for structure delineation during treatment planning, it is both time consuming and prone to inter‐ and intraobserver contour variability …”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic and extrinsic factors can limit the ability to delineate anatomical regions for different imaging modalities due to poor soft tissue contrast, noise, and image artifacts. In addition, manual contours have interobserver delineation variability (due to different perception of observers), and intraobserver delineation variability (rooted in different interpretations/perception of the same observer in different trials). Observer variability is one of the dominant geometric uncertainties in radiation therapy, nonetheless, manual contours are considered the gold standard.…”
Section: Introductionmentioning
confidence: 99%